Evaluasi Kapasitas Saluran Eksisting terhadap Debit Limpasan sebagai Kajian Perancangan Saluran Drainase di Perumahan Sukawinatan Permai Indah - Septarianti Arini; Radius Pranoto (Jurnal Talenta Sipil, 2026)
The rapid expansion of residential areas in Palembang City through swamp land reclamation without the application of eco-drainage principles has increased the occurrence of local flooding by reducing natural infiltration capacity. This condition has significantly affected the Sukawinatan Permai Indah Residential Area, where inundation and drainage overflow frequently occur during heavy rainfall. This study evaluates the hydraulic performance of the existing drainage network in conveying the design storm runoff within the residential area. A quantitative approach was adopted using annual maximum daily rainfall data for the period 2013–2022 obtained from the Meteorological, Climatological, and Geophysical Agency (BMKG). Design rainfall was estimated using the Log Pearson Type III distribution, while peak runoff discharge was calculated using the Rational Method. The analysis produced a 10-year return period rainfall of 173.76 mm. Hydraulic evaluation revealed that the existing drainage system is incapable of conveying the design runoff because of inadequate channel dimensions, structural deterioration, and significant sediment deposition. The average runoff discharge along the drainage reaches was 0.0037 m³/s, the maximum discharge reached 0.0327 m³/s, and the cumulative discharge at the outlet was 2.5536 m³/s. These findings indicate that the existing drainage network requires substantial improvement. Accordingly, the drainage system should be redesigned and reconstructed based on hydraulic design standards while incorporating eco-drainage principles to enhance runoff management. In addition, regular inspection and maintenance are essential to ensure the long-term effectiveness and sustainability of the drainage system in mitigating urban flooding.